Nanoparticles Targeting Macrophages as Potential Clinical Therapeutic Agents Against Cancer and Inflammation - Hu, Guorong; Guo, Mengfei; Xu, Juanjuan; Wu, Feng; Fan, Jinshuo; Huang, Qi; Yang, Guanghai; Lv, Zhilei; Wang, Xuan; Jin, Yang (Frontiers in Immunology, 2019)
With the development of nanotechnology, significant progress has been made in the design, and manufacture of nanoparticles (NPs) for use in clinical treatments. Recent increases in our understanding of the central role of macrophages in the context of inflammation and cancer have reinvigorated interest in macrophages as drug targets. Macrophages play an integral role in maintaining the steady state of the immune system and are involved in cancer and inflammation processes. Thus, NPs tailored to accurately target macrophages have the potential to transform disease treatment. Herein, we first present a brief background information of NPs as drug carriers, including but not limited to the types of nanomaterials, their biological properties and their advantages in clinical application. Then, macrophage effector mechanisms and recent NPs-based strategies aimed at targeting macrophages by eliminating or re-educating macrophages in inflammation and cancer are summarized. Additionally, the development of nanocarriers targeting macrophages for disease diagnosis is also discussed. Finally, the significance of macrophage-targeting nanomedicine is highlighted, with the goal of facilitating future clinical translation.